SISTEM INFORMASI PENJUALAN PADA DEPOT KAYU SERASAN JAYA 3 DENGAN METODE PENGEMBANGAN EXTREME PROGRAMMING - Areyanda Listianto; Suhartini; Fajriyah (STEKOM PRESS, 2023)
Serasan Jaya 3 Building Materials Wood Depot is a business engaged in the sale of building material products, especially wood. Until now the Serasan Jaya 3 Building Materials Timber Depot only uses a manual sales and transaction system, which in this case requires a new breakthrough to keep up with technological developments that are developing in the current era because basically almost all ages demand something practical and easier. By looking at some of the existing problems, the researcher tries to design and build an information system for selling goods at the Serasan Jaya 3 Building Materials Wood Depot based on Android, therefore, the author chose this topic for a thesis entitled